Rapid morphological change in an urban bird due to COVID-19 restrictions - Eleanor S. Diamant; Pamela J. Yeh (Proceedings of the National Academy of Sciences, 2025)
The COVID-19 pandemic provided a natural experiment to test the impacts of human activity on urban-dwelling wildlife. Urban dark-eyed juncos differ in bill shape and size in Los Angeles in comparison to local wildlands. We measured juncos that hatched before, during, and after COVID-19 restrictions at a Los Angeles college campus. Birds that hatched during and soon after COVID-19 restrictions had bills that resembled those of local wildland birds. Yet, bills rapidly returned to pre-COVID-19 morphology in birds hatched in the years following pandemic restrictions. Thus, human activity (and lack thereof) underlies rapid morphological change in an urban bird.